Performance of Trichograma spp in small tomato borer (Neoleucinodes elegantalis Guenée): Pest management with egg parasitoid - José Romário de Carvalho; Luis Moreira de Araujo Junior; Dirceu Pratissoli; Débora Fragoso; Amanda Túler (Acta Scientiarum. Biological Sciences, 2020)
The tomato is a crop of great importance for Brazilian agriculture. Among the most damaging pests, the small tomato borer, Neoleucinodes elegantalis Guenée (Lepidoptera: Crambiadae) has caused great losses, since they directly reach the fruits to be commercialized, being used for its handling a large volume of insecticides. In this way, the use of alternative techniques that help in the management of this pest becomes of great importance. Among them, the use of the egg parasitoid Trichogramma spp. has been promising. Thus, the present study aimed to evaluate the performance of Trichogramma species and/or strains in N. elegantalis by selection of strains. The selection was made based on four lineages maintained in the Nucleus of Scientific and Technological Development in Phytosanitary Management of Pests (NUDEMAFI), being three strains of the species T. pretiosum and one of T. galloi species. The parameters evaluated were percentage of parasitized eggs, egg viability, number of individuals per eggs, sex ratio and number of Trichogramma spp. to be released. The T. galloi (T. g1) showed the best parameters for selection of the strain. Estimating the optimal number of T. g1 in eggs of small-fruit-borer was 82 individuals per egg parasitoid. Therefore, this strain was selected for the management of the small tomato-borer, whose eggs presented favorable physicochemical characteristics for the development of the parasitoid.